Identification and expression analysis of PAL genes related to chlorogenic acid synthesis in Vaccinium dunalianum Wight - An, Xiuhua; Li, Guoze; Chen, Aiyi; Zhao, Ping; Ding, Yong (Frontiers in Plant Science, 2025)
Phenylalanine ammonia-lyase (PAL) is the first key enzyme in the metabolic pathway of phenylpropanoid. Chlorogenic acid (CGA) is an important secondary metabolite in the phenylpropanoid metabolic pathway of plants. However, the role of the PAL gene in CGA biosynthesis in Vaccinium dunalianum Wight is still unclear. In this study, seven PAL genes (VdPAL1–VdPAL7) were cloned and analyzed through full-length transcriptome sequencing combined with reverse transcription polymerase chain reaction (RT-PCR) amplification in V. dunalianum. Bioinformatics analysis revealed that the seven VdPAL genes contain complete open reading frames (1,860–2,148 bp) encoding hydrophilic proteins of 619–715 amino acids, with molecular weights ranging from 67.44 to 77.70 kDa. The VdPAL proteins contain the PLN02457 domain, with the secondary structures predominantly composed of α-helices and the tertiary structures exhibiting a characteristic “hippocampus” conformation. Phylogenetic analysis grouped these VdPAL genes into three subfamilies: VdPAL1, VdPAL3, and the VdPAL2/4/5/6/7 cluster. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) analysis showed that the expression levels of the VdPAL1 and VdPAL4/5/6/7 genes were significantly higher in both tender and mature leaves, in flower buds, flowers, green and red fruits, and in green and red fruit stems than those of VdPAL2 and VdPAL3. In the same tissue type, except for VdPAL2, the expression levels of the other six PAL genes were significantly higher in young tissues compared with mature tissues. The PAL gene family mediates the biosynthesis of CGA in V. dunalianum, with the combined expression of VdPAL1/2/4/5/6/7 showing a positive correlation with the CGA content across the analyzed tissues. These results provide experimental evidence for understanding the composition, structural characteristics, and biological functions of the PAL genes in V. dunalianum.